Breeding expansion of sandhill cranes in Quebec. Issue 3 (11th January 2022) - Casabona I Amat, Clara; Adde, Antoine; Mazerolle, Marc J.; Lepage, Christine; Darveau, Marcel
Abstract: Sandhill cranes ( Antigone canadensis ) were broadly extirpated from much of their historical range in North America at the beginning of the twentieth century. Various conservation‐related legislation, such as the United States Migratory Bird Treaty Act, have assisted with population recovery. The eastern population of sandhill cranes has been growing rapidly since the 1980s and is thought to have expanded its geographic range to Quebec, Canada. Understanding the colonization and habitat use by the species in previously unoccupied breeding areas is necessary to develop and apply management measures. Using a dynamic occupancy modeling approach, we investigated the recent colonization and extirpation patterns of sandhill cranes in Quebec from 2004–2019. We combined data from 3 data sets (helicopter surveys, breeding bird atlas surveys, and eBird) to increase the spatial coverage and the number of species occurrence records while accounting for imperfect detection probability. Detection probability was highest for the helicopter survey (0.70), whereas the 2 other data sets had relatively low detection levels (0.10–0.26). Based on a simulation study, we found that excluding the eBird data from the analysis produced more biased estimates than excluding the atlas and helicopter survey data sets. Throughout the study, sandhill cranes seemed to have completed their colonization of western Quebec and only recently started to nest in eastern areas. Initial occupancy increased with wetland cover and colonization probability increased weakly with the cover of agricultural areas, suggesting that in our study area sandhill cranes rely essentially on natural wetlands during the breeding season. Abstract : We studied the occupancy dynamics of sandhill cranes in southern Quebec, Canada, from 2004–2019, integrating 3 data sets to account for imperfect detection probability. Our results indicate that occupancy by sandhill cranes in our study area is low during the breeding period but that the species expanded eastward into unoccupied and available open wetlands, regardless of the amount of agricultural areas in 10‐km × 10‐km cells.